International review of behaviour change initiatives. Climate change behaviours research programme. - Southerton, Dale; McMeekin, Andrew; Evans, David (My University, 2011)
The report reviews a range of behaviour change initiatives that have attempted to reduce the carbon intensity of consumption practices. It aims to enhance understandings of the different combinations of mechanisms for behavioural change, and to explore the potential transferability of initiatives to other regional, specifically Scottish, contexts. It focuses on six initiatives: the Durham Water project in Ontario/ Canada, the TravelSmart campaign in Australia, the Residential Energy Conservation Ordinance (RECO) in Berkeley/ USA, Barclays Cycle Hire in London, the project FoodNYC in New York City/ USA and the Middelgrunden Wind Cooperative in Copenhagen/ Denmark.
Keywords: Individualverkehr; Fahrradverkehr; Verhaltensänderung; Kampagne; Öffentliches Fahrradverleihsystem; Fahrradverleih; Nachhaltige Mobilität; Fallstudie; Best Practice